THE INFLUENCE OF JOB INSECURITY AND JOB STRESS TOWARD ABSENTEEISM AT KPU MINAHASA TENGGARA - Benu, Nada Astria Carmel Benu A.C. Benu; Pangemanan, Sifrid S.; Saerang, Regina T. (Universitas Sam Ratulangi, 2019)
Abstract: Absenteeim is the absence of someone at work. In Indonesia, especially for the State Civil Service (ASN), absenteeism will affect their salary or income. According to previous research, absenteeism has a relationship with job stress and job insecurity. Job stress is a condition of constancy that creates a physical and psychological imbalance, which affects emotions, thought processes, and the condition of an employee. Job insecurity is the powerlessness to guarantee the continuity of work or its components when the work situation is threatened, and creates insecurity for employees, or insecurity felt by employees. This research uses quantitative methods. The sample of this study were all respondents of KPU Minahasa Tenggara. This research uses purposive sampling and the date is filled in by 30 respondents. The results of this study indicate that simultaneous Job Insecurity and Job Stress have a significant effect on Absenteeism, Job Insecurity does not significantly influence Absenteeism in the Southeast Minahasa KPU partially, and Work Stress behavior has a significant effect on Absence in the Southeast Minahasa KPU partially. The recommendation is for the Southeast Minahasa KPU to focus more on knowing what drives Work Stress in the Southeast Minahasa KPU and the impact on absenteeism from the office. As frequently mentioned by companies, managers and employees must work together to find out what is best for the company. Keywords: job stressÂ